(untitled) (Journal of Pakistan Orthopaedic Association, 2014)
Background: Lateral epichondylitis is a painful condition caused by overuse of common extensor muscles of elbow, when performing any repetitive activity, not just tennis. The mainstay of treatment is corticosteroid injections, though their effectiveness has not been well established by controlled studies. Objective: The objective of this study was to assess the efficacy of steroid injection in terms of pain relief in patients with lateral epicondylitis / tennis elbow at the common extensor tendon origin. Study Design: Descriptive Cross-Sectional Study. Place and Duration of Study: The study was carried out at OPD of Orthopaedics unit II, Jinnah Hospital Lahore from May 2012 to November 2012. Subjects and Methods: 60 patients suffering from tennis elbow fulfilling the inclusion criteria were included in the study. All the patients received single dose of corticosteroid injection and Visual Analogue Scale assessed the outcome at 4th week interval in terms of pain relief. The main outcome variable, efficacy was described as frequency distribution table. Results: Out of sixty patients in the study, intervention was effective in 54 (90.0%) patients (VAS=0) and was not effective in 6 (10.0%) patients. (VAS = 1- 6). Conclusion: Corticosteroid injection for the treatment of Tennis Elbow is very high. So, it is recommended that it should be used as first line therapy as treatment for tennis elbow. Key Words: lateral epicondylitis, Tennis elbow; steroid injection; visual analogue scale.